The lost post: Mikhail Tsekhanovskii's sound version of The Post (Pochta, 1930). (2nd January 2016) - Izvolov, Nikolai
Abstract: This is the first publication of the editing list for the lost sound version of Mikhail Tsekhanovskii's animated cartoon The Post ( Pochta, aka The Mail, 1930), which Nikolai Izvolov discovered in the Film Institute VGIK in 2013. Izvolov introduces the film and its distribution history in the early 1930s, before discussing the peculiarities of Tsekhanovskii's sound version of the film, which is 10 minutes longer than the silent version and includes a prologue in the form of a cabaret; the text is written by Daniil Kharms. The publication of the dialogue sheets follows this introduction.